Contextual-Based E-Comic Media Through Maritime Thematic Learning In Early Childhood - Samad, Farida; Wondal, Rosita; Samad, Rita; Arfa , Umikalsum (Jurnal Ilmiah POTENSIA, 2025)
This research aims to analyze the use of contextual-based e-comics through marine thematic learning in early childhood marine. Through this research, the problem will be solved by using e-comic learning media integrated into marine thematic learning for children aged 5-6 years at PAUD Bhayangkari Ternate City. The research uses a mixed method. While the design used to develop teaching materials is the 4-D model design, the development stages used are the development stages of Thiagarajan, Semmel & Semmel (1974) which include four development stages namely define, design, develop, and disseminate. The data that has been collected using the instruments above is then analyzed quantitatively and directed to explain the validity of the comic media developed. Data from the validation of experts were analyzed by considering input, comments, and suggestions from validators. The results of the analysis were used as guidelines for revising the developed learning media. The data analysis methods used in this development research are the qualitative descriptive analysis method and the quantitative descriptive method. This method is used to process data from the results of linguists, learning media experts, and individual and small-group trial experts. To be able to support the learning process at PAUD Bhayangkari, the e-comic media goes through the expert validation test stage (media experts, linguists, PAUD material experts) as well as product trials (small group tests) where all three experts give very good or valid assessments and student responses as subjects classified as very good. From media experts, the percentage of validity obtained is 89.2, from users with a percentage of 98.33, linguists the percentage achieved is 100. From this analysis, as foundational years for cognitive and social development, early childhood education plays a pivotal role in shaping future learning experiences. Integrating engaging and relevant materials, such as e-comics, can enhance children's interest and understanding of marine themes.